Synergism of endophytic Bacillus subtilis and Klebsiella aerogenes modulates plant growth and bacoside biosynthesis in Bacopa monnieri - Shukla, Namita; Singh, Deepti; Tripathi, Arpita; Kumari, Poonam; Gupta, Rahul Kumar; Singh, Shiwangi; Shanker, Karuna; Singh, Akanksha (Frontiers in Plant Science, 2022)
Bacopa monnieri is a main source of pharmaceutically important bacosides; however, the low content of these molecules in planta remains a limiting factor for fulfilling the industrial requirement. The accumulation of secondary metabolites can be enhanced in plants upon inoculation with endophytes. In this study, we isolated and analyzed the culturable endophytes associated with different plant parts. By analyzing their impact on plant growth parameters (in vitro and in vivo) and Bacoside A content, we found few candidates which increased bacoside accumulation significantly. Finally, two promising endophytes namely Bacillus subtilis (OK070745) and Klebsiella aerogenes (OK070774) were co-cultivated with B. monnieri cuttings singly as well in combination mode to clarify their effect on bacoside biosynthesis and accumulation in B. monnieri shoot. Consortium inoculated plants significantly enhanced the plant biomass and Bacoside A content with respect to single inoculation. The results of real-time quantitative (RT-PCR) revealed significant accumulation of bacoside biosynthetic pathway transcripts (HMGCR, PMVK, FDPS, SQS and β-AS) in case of plants inoculated with microbial combination while the single inoculation of B. subtilis diverted the plant’s machinery towards the synthesis of phenylpropanoid genes like CCR, CAD, CHS and HST. In addition, higher expression of MYB 2 and WRKY 1 transcription factors in combinational treatment points out towards their probable role in better physiological and developmental processes. Altogether, this is the first study on B. monnieri endophytes interaction showing improvement in accumulation of bacoside A by modulating various genes of metabolic pathway and thus suggests an effective “green approach” for augmenting in planta production of pharmaceutically important bacosides.